The Development of Semantic Dictionary Prototype for the Balinese Language - Cokorda Pramartha; I Made Yoga Mahendra; Gede Primahadi Wijaya Rajeg; I Wayan Arka (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2023)
The Balinese language is the mother tongue that is used by the people who live in Bali for daily communication and social interaction. Currently, the Balinese language just like many other mother tongue languages in Indonesia is in the process of being abandoned by the younger generation for many reasons for instance it is because there are limited resources available on the Internet.  Semantic ontology has been chosen as the backbone of this system due to minimising the ambiguity of the translation using the keyword-based query.  The development utilises the prototyping system development approach by focusing on the involvement of the user at every stage of development.  The system has three main features namely semantic browsing, semantic searching, and antonym searching.  We carried out two types of evaluation (functional and non-functional) by involving 30 participants and the results show users perceive the usefulness and ease of use to be positive